2016
DOI: 10.1177/0269215515602136
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the impact of stroke on social support and social networks: associated factors and patterns of change

Abstract: Objective: Identify what factors are associated with functional social support and social network post stroke; explore stroke survivors' perspectives on what changes occur and how they are perceived. Data sources:The following electronic databases were systematically searched up to May 2015: Academic Search Complete; CINAHL Plus; E-journals; Health Policy Reference Centre; MEDLINE; PsycARTICLES; PsycINFO; and SocINDEX.Review methods: PRISMA guidelines were followed in the conduct and reporting of this review. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
181
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(188 citation statements)
references
References 84 publications
(453 reference statements)
7
181
0
Order By: Relevance
“…A recent systematic review of 70 research reports exploring the impact of stroke on social support found that after stroke contact with friends and involvement in social activities reduced, and there was strain within the family unit (Northcott, Moss, Harrison, & Hilari, 2015). Further, there was a consistent association between poor social support and feeling depressed (13/14 studies); aspects of the social network were also associated with depression (7/8 studies) (Northcott et al, 2015). For example, in one study having few social contacts outside the house was found to be the strongest predictor of depression in stroke survivors at 12 months, two years and three years follow up (Astrom, Adolfsson, & Asplund, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review of 70 research reports exploring the impact of stroke on social support found that after stroke contact with friends and involvement in social activities reduced, and there was strain within the family unit (Northcott, Moss, Harrison, & Hilari, 2015). Further, there was a consistent association between poor social support and feeling depressed (13/14 studies); aspects of the social network were also associated with depression (7/8 studies) (Northcott et al, 2015). For example, in one study having few social contacts outside the house was found to be the strongest predictor of depression in stroke survivors at 12 months, two years and three years follow up (Astrom, Adolfsson, & Asplund, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…People with aphasia are excluded from most stroke research exploring social networks (Northcott et al, 2015). Even where people with aphasia have been included, often researchers have relied on proxies (Astrom et al, 1993;Boden-Albala et al, 2005) although there are concerns that proxy responses are not commensurate with self-report (Hilari, Owen, & Farrelly, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Social support influences mental health conditions [4], and a high level of social support from family members improves the functional status, and thus, the mental health of patients with stroke [5]. Spirituality is considered to be the essence of one's being and gives meaning and purpose to our existence [6].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Additionally, aphasia impacts psychosocial health as many persons with aphasia report increased depression, social isolation, and decreased quality of life. [6][7][8][9][10][11][12][13] Due do the confluence of these many factors, persons with aphasia and family members seek out treatment and support. ICAPs are one type of service that may address some of those issues.…”
Section: The Impact Of Aphasia After Strokementioning
confidence: 99%
“…50 Northcott and colleagues found that reduced social networks following stroke and aphasia was associated with depression. 12 A literature review by Attard and others found that comments from participants in community aphasia groups could be grounded in psychological well-being domains. 51 Comments reflected that groups provided a means to form positive relations with others and to have a purpose in life.…”
Section: Comprehensiveness Of Aphasia Treatmentmentioning
confidence: 99%